Photocatalytic reduction of CO2 on Pt2+–Pt0/TiO2 nanoparticles under UV/Vis light irradiation: A combination of Pt2+ doping and Pt nanoparticles deposition. (24th August 2015) - Xiong, Zhuo; Wang, Haibing; Xu, Nuoyan; Li, Hailong; Fang, Baizeng; Zhao, Yongchun; Zhang, Junying; Zheng, Chuguang
Abstract TiO2 nanoparticles modified by Pt2+ ions and Pt nanoparticles (Pt2+–Pt0/TiO2) were synthesized through a simple sol–gel method. The physical-chemical characteristics of the catalysts were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscope, UV–Vis absorbance spectroscopy, and photoluminescence spectroscopy. Pt2+ ions were doped into the lattice of TiO2 and Pt nanoparticles were deposited on the surface of TiO2. Photocatalytic reduction of CO2 with water vapor under ultraviolet (UV) and visible light irradiation was conducted in a continuous-flow reactor. Loading of Pt2+ and Pt0 with appropriate ratio effectively enhanced the yields of H2 and CH4 but showed no significant effect on the production of CO. The highest yield of CH4 reached 264.5 and 138.6 μmol g-cat−1 after UV and visible light irradiation for 7 h, respectively. The enhanced activity of Pt2+–Pt0/TiO2 catalyst may be due to the low recombination rate of photogenerated electron–hole pairs caused by Pt nanoparticles and the strong visible light absorption, as well as the high surface area induced by Pt2+ ions.